Efficacy of Diferent Formulations of Bromodiolone-based Rodenticides Against Rodent Pests in Alfalfa - Goran Jokić; Marina Vukša; Ibrahim Elezović; Bojan Stojnić; Suzana Đedović (Pesticidi i Fitomedicina, 2010)
In order to compare the efficacy of different formulations of Bromodiolone-based rodenticides against mixed populations of common vole (Microtus arvalis Pall) and striped field mouse (Apodemus agrarius) in alfalfa, the testing was conducted using the standardEPPO method at the locations of Belegiš and Putinci, in summer of 2010. The experimental design consisted of a completely randomized block with four replicates and with the main plot area of 400 m2. The abundance and distribution of small rodents populations at theexperimental plots were determined on the basis of appearance and spatial distribution of active holes. The efficacy of different odenticide formulations was evaluated according to the number of active holes 7, 14, and 28 days after treatment (DAT), using the Henderson-Tilton’s formula. The testing was done with the commercially available rodenticide formulations: AB (grain-based baits), RB (ready-to-use baits – pouches) and PT (pellets), ontaining0.005% of active ingredient Bromodiolone. The monofactoral analysing of variance did not result in any statistically significant ifferencein efficacy of rodenticide formulations 7 DAT at the Belegiš locality and 7 and 14 DAT at the Putinci locality. But, the tatistically significant difference in efficacy of rodenticide formulations was observed at Belegiš locality on the 14th day of the experiment. Also,at the end of experiment, the efficacy of rodenticide formulations significantly varied at both locations. Nominally, the lowest efficacy of 72.5% was exhibited by AB ormulation,while the average efficacy of RB and PT formulations against mixed populations of common vole and striped field mouse in alfalfa was 88.3% and 77.7%, respectively. It is concluded that the use of RB formulation of Bromodiolone-based rodenticides can improve the control of rodent pests in alfalfa.